Diverse reactivity of carbenes and silylenes towards fluoropyridines - Kundu, Gargi; Ajithkumar, V. S.; Bisai, Milan Kumar; Tothadi, Srinu; Das, Tamal; Vanka, Kumar; Sen, Sakya S. (Chemical Communications, 2021)
The reaction of IDipp with C5F5N led to functionalization of all three carbon atoms of the imidazole ring with HF2- as the counter-anion (1). Reactivity with 2,3,5,6-tetrafluoropyridine gives only C-F bond activation leaving C-H bonds intact (5b). The reaction of SIDipp with C5F5N in the presence of BF3 afforded the ring cleavage product (3). Analogous reactions with silylene led to oxidative addition at the Si(II) center.

Development of six-membered saturated cyclic diaminocarbenes in main-group chemistry - Kundu, Gargi; Sen, Sakya S. (Dalton Transactions, 2025)
In recent years, there has been a remarkable surge in the utilization of saturated N-heterocyclic carbenes (NHCs) as ligands in main group chemistry. While the field has predominantly focused on five-membered NHCs and cyclic alkyl(amino) carbene (CAAC) ligands, the investigation of six-membered NHCs (6-NHCs) has only just begun. Despite possessing higher nucleophilicity than their five-membered counterparts, 6-NHCs have been less explored due to their lack of structural rigidity. This feature article aims to highlight recent developments in 6-NHCs in only main group chemistry. Exciting new studies have demonstrated the activation of B-H bonds in HBpin, ring expansion from a six-membered to a seven-membered ring under ambient conditions, and the stabilization of transient units ``H-B 00000000 00000000 00000000 00000000 11111111 00000000 11111111 00000000 00000000 00000000 O'' and ``(OH)BO'', among other intriguing phenomena. A major focus of this review is on synthetic approaches for 6-NHC-stabilized main-group compounds and their unusual properties, as revealed by spectroscopic and crystallographic data. While the chemistry of 6-NHCs is still in its nascent stage, the findings presented in this feature article underscore the need for its exploration and further investigation. Furthermore, this review provides valuable insights into effective synthetic methods for creating new 6-NHCmain group (B, Al, Si, P, Zn, etc.) complexes, along with mechanistic explanations for some of these reactions. These advances hold great promise for the future development of this exciting and rapidly evolving field of N-heterocyclic carbene chemistry.